The barzakh and the bardo: challenges to religious violence in Sufism and Vajrayana Buddhism - Woodhull, Jennifer Green (Department of Religious Studies, 2020)
In the twenty-first century, religious violence has become endemic in our world. Scholars are divided on the true motivations for such violence, however. While some perceive inherent incitements to violence embedded in religion itself, others blame other factors—primarily, competition for resources, which then co-opts religious feeling in order to justify and escalate conflict. This dissertation proposes that more fruitful answers to the riddle of religious violence may lie in the relationship between collective identity and religious allegiance. Identity construction is liminal and, as such, experiential. Hence, this study applies the analytical lens of liminality to explore possible understandings of religious violence. Taking the position that liminal passages are natural and unavoidable aspects of lived experience, it argues that the fixation on doctrinal certainties and religious ideals common among perpetrators of religious violence functions largely to oppose the ambivalence and uncertainty characteristic of liminality. It further posits the hypothetical phenomena of reactive projection and autonomic liminality as reactions to liminal experience, leading to eruptions of violence. The Tibetan Buddhist bardo and Sufi barzakh constitute religiously sanctioned instances of liminality. Although these passages are conventionally perceived as postmortem locales, both systems include broader metaphysical understandings, making their transformative potential profoundly relevant to spiritual practice during this lifetime. I argue that a close reading of the bardo and the barzakh demonstrates the capacity of religious tradition to offer compelling alternatives to the fixation on the extreme views typically implicated in religious violence. I further propose that the nondualistic, inclusive worldview implicit in understandings of the bardo and barzakh may prove useful in promoting a practice of “reflective interiority”—not only in disrupting the rigid mindset of those moved to perpetrate religious violence, but also in shifting the moral fixity sometimes associated with the scholarship on religious violence.